'It feels like my metabolism has shut down'. Negotiating interactional roles and epistemic positions in a primary care consultation - Olaug S. Lian; Sarah Nettleton; Huw Grange; Christopher Dowrick (Wiley, 2023)
Abstract Introduction Our aim is to explore the ways in which a patient and a general practitioner (GP) negotiate knowledge claims stemming from different epistemic domains while dealing with a mismatch between experiential and biomedical knowledge during the clinical consultation. We interpret their interaction in relation to the sociocultural context in which their negotiation is embedded and identify factors facilitating their successful negotiation (a medical error is avoided). Methods Based on a narrative analysis of a verbatim transcript of a complete naturally occurring primary care consultation, we explore the moment‐to‐moment unfolding of talk between the patient and the GP (two women). Findings The patient experiences symptoms of what she interprets as a thyroid condition, and indirectly asks for medication. She presents her case by drawing on experiential knowledge ('it feels like my metabolism has shut down') and biomedical knowledge (while suggesting a diagnosis and a diagnostic test). The GP informs her that her thyroid blood tests are normal and uses biomedical knowledge to explain why she turns down the patient's request. This stages a potential conflict between the patient's embodied experiential knowledge and the doctor's biomedical knowledge. However, during their encounter, the patient and the GP manage to co‐construct the patient's illness story and make shared decisions about further actions. Conclusion The transition from potential conflict to consensus is a result of the mutual efforts of two parties: a patient who persistently claims experiential as well as biomedical knowledge while at the same time deferring to the GP's professional knowledge, and a GP who maintains her epistemic authority while also acknowledging the patient's experiential and biomedical knowledge. Patient and Public Contribution Our empirical data are sourced from a data archive and patients were not involved in the design or conduct of the study, but our study is based on a naturally occurring clinical consultation with a patient.